Clinical Dental Learning Environment: Exploring Challenges and Strategies for Improvement - Hafsa Bibi; Bushra Mehboob; Fatima Abdul Qaiyum; Tahira Amjad; Munazza Baseer; Amara Hayat Awan (Journal of Gandhara Medical and Dental Sciences, 2025)
OBJECTIVES